PENERAPAN PIDANA PADA TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN YANG DILAKUKAN SECARA BERSAMA-SAMA : Studi Perbandingan Putusan Nomor: 976/Pid.B/2018/Pn.Pdg dan Putusan Nomor 890/Pid.B/2018/Pn.Pdg - Rangga Prayitno; Iyah Faniyah; Wirna Rosmelly (Ekasakti Jurnal Penelitian dan Pengabdian, 2020)
The crime of theft with a weight that is carried out jointly as regulated in Article 363 and Article 365 of the Criminal Code is called theft with qualifications. Theft with a weighting carried out jointly in Decision Number: 976 / Pid.B / 2018 / Pn.Pdg and Number 890 / Pid.B / 2018 / Pn.Pdg by using a comparison of the verdict where in the Decision Number: 976 / Pid. B / 2018 / Pn.Pdg, the two defendants were punished with different sentences while in Decision Number 890 / Pid.B / 2018 / Pn.Pdg was punished with the same sentence, even though the articles applied were the same Article 363 Paragraph (1) the 4th Criminal Code.